‘The Need for Whitewash and Disinfectant’: Eoghan McTigue’s All Over Again - Emma Grey (Review of Irish Studies in Europe)
Eoghan McTigue’s exhibition entitled All Over Again documents the erasure of several republican and loyalist murals in Belfast between 2001 and 2003, prior to the launch of the ‘Re-imaging Communities’ project and explores the discrepancy between post-Agreement Northern Ireland’s perceived abnormality and the desire for it to be ‘normal’ again.